El absolutismo y la Constitución de Cádiz: consideraciones sobre la gestación del «poderresponsable» en la crisis del Antiguo Régimen El absolutismo y la Constitución de Cádiz: consideraciones sobre la gestación del «poderresponsable» en la crisis del Antiguo Régimen - Noelia González Adanez (Política y Sociedad, 2003)
This article tries to explore the discourses employed in the transition from the ancien regime to the constitutional monarchy in Spain. The ancien regime, in its late stages, is analysed as providing new spheres for negotiation; the constitutional monarchy is seen as a political system arised from new demands addresed to guarantee authority’ representation and responsability. In Spain, the constitutional revolution, founded in a catholic anthropology, gave rise to a particular mode of citizenship entirely dependent on the principle of national sovereignity which had sprung from the constitutional debates. These processes are taking place, also in the rest of West Europe, in a time of discourse change characterized by the confrontation between two different paradigms or approaches of the individual and its relation with society: juridical and civil. El presente artículo pretende explorar las vías discursivas por las que transita el antiguo régimen hacia la monarquía constitucional El primero es conceptualizado como un modelo político en el que la monarquía se adapta y desarrolla espacios para la negociación, y el segundo como un sistema que surge progresivamente de la introducción de la representatividad y responsabilidad de la autoridad como exigencias irrenunciables. Esto último se verificó en virtud de una revolución constitucional que, desde la matriz cultural